Impact of chemical agents for surface treatments on microhardness and flexural strength of root dentin - Marcelino, Ana Paula Marcheto; Bruniera, João Felipe; Rached-junior, Fuad Abi; Silva, Silvio Rocha Corrêa da [UNESP]; Messias, Danielle Cristine (Sociedade Brasileira de Pesquisa Odontológica - SBPqO, 2014)
This study assessed the cross-sectional Knoop microhardness and flexural strength of root dentin exposed to different surface treatments with chemical agents after biomechanical preparation. Root canals from human canines were biomechanically treated and divided into eight groups (n=10) to receive one of the following dentin treatments: I. Deionized water (control); II. 5.25% Sodium hypochlorite (NaOCl); III. NaOCl + 10% Sodium ascorbate (SA); IV. SA; V. 2% Chlorhexidine gel (CHX); VI. 37% Phosphoric acid gel (PA) + CHX; VII. PA; and VIII. PA + NaOCl. The roots were sectioned to obtain specimens that were evaluated for cross-sectional Knoop microhardness and flexural strength using a three-point bending test. ANOVA and Tukey’s test were performed. The microhardness in the control group was significantly higher (p < 0.05) than in the groups exposed to chemical agents, which in turn were statistically similar (p > 0.05) to each other. Regarding flexural strength, PA+NaOCl provided statistical higher values than PA+CHX and CHX. However, there was no significant difference between the control group and those groups subjected to surface treatment (p > 0.05). Dentin microhardness was reduced after exposure to NaOCl, CHX, PA, SA and their associations and the flexural strength of radicular dentin was not affected by the chemical agents.
Keywords: Chemical Compounds; Physical Properties; Dentin